Integrating Technology and Ethnophysics to Support Sustainable Education and Cultural Preservation through Traditional Games of Gasing and Hula Hoop in Rotational Physics Learning - Syahani Tazkya Mardatillah; Sofyarani Karunia Shanty; Nasihatin Auliya; Nurita Apridiana Lestari; Iqbal Ainur Rizki (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: This study explores the rotational physics concepts embedded in traditional children's games, specifically gasing (pulling tops) and hula hoops, to support sustainable education and cultural preservation. The research integrates ethnophysics and technological analysis to examine how these games can be utilized in contextual and meaningful physics learning. Method: This research used a qualitative exploratory approach to map physical phenomena in traditional games. Data were collected through purposive sampling involving two participants with expertise in playing gasing and hula hoop. Data collection methods included observation, interviews, and literature review. To support deeper analysis, digital technology such as slow-motion video recording, motion-tracking applications (e.g., Phyphox), and angular velocity sensors were used to visualize and quantify rotational motion. Results: The findings indicate a strong correlation between the mechanics of traditional games and the principles of rotational motion, such as torque, angular velocity, moment of inertia, and conservation of angular momentum. Both gasing and hula hoop exhibit consistent patterns of rotation around a fixed axis, which are fundamental concepts in rotational dynamics. Technology integration allowed for enhanced visualization and interpretation of motion parameters, enriching the learning process. Novelty: The study offers a novel interdisciplinary approach by combining local cultural practices with digital technology to facilitate physics learning. It bridges traditional knowledge with modern scientific tools, supporting SDG 4 (Quality Education) and SDG 11 (Sustainable Cities and Communities). This ethnophysics-based framework contributes to culturally responsive pedagogy and digitalized STEM education.